An Analysis on Students’ Errors in Determining Past Regular and Irregular Verb at Second Grade of SMP Negeri 1 Bintan - Taufik Afdal; Eka Mayasari; Riko Agus Prasetio (IALLTEACH (Issues In Applied Linguistics & Language Teaching), 2022)
This research aims to investigate students’ errors in determining past regular and irregular verbs. The formulation of the problem in this research are: 1. How is students’ ability in using past regular and irregular verb form? 2. Which past verb form is mostly misused? This research is about analyzing students’ errors at second grade of SMP Negeri 1 Bintan. The population of this research were 245 students. The researcher only took 32 students as the subject of the research. There is 1 test instrument used to collect the data. The researcher distributed the test in the form of daily conversation. To analyze the data, researcher classified the students’ errors into excellent, good, fair, and poor. After analyzing the data, it was discovered that the mean score of students’ ability is 75 which means that students’ ability in determining past regular and irregular verb belongs to good category. While, the mostly misused past verb form is irregular verb. This is because irregular verb differs from the regular tense form. It is suggested that students should memorize about the past irregular verb and should know the formula in the regular verb.